SUCCESSION PROCESS IN FAMILY BUSINESS: A STUDY ON THE MANUFACTURE OF RICE MILL IN ACEH BESAR DISTRICT - Isnaniati; Fajri; Nugroho A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
Agricultural sector companies in Aceh especially in Aceh Besar are owned by families, one of which is a company in the field of rice milling industry. The company has an important role to meet the needs of food and employment. So for the family business should be successful and long-lived. One way is by preparing a successor through the succession process. The succession process can be carried through; (1) determination of the criteria for a successor (2) the development potential successor, (3) the involvement of potential successor in the family business. The design of the study is a qualitative method, therefore the results in this study cannot be generalized for other family businesses. 92.27% of candidates for successor have criteria acceptable, charismatic, energic, managing, achieving and networking, 69.44% or most of family business leaders develop a candidate of successor and 75% or most of prospective successors are involved in every business activity. The results in this study indicate that the successor is ready to replace the founder or manager as a family business leader.